Studying the level of dialogical speech development in pupils with intellectual disorders as an indicator of their mental health - O. Haiash; S. Mykhalska; S. Myronova; O. Bielova (Zaslavsky O.Yu., 2024)
Background. The research was aimed at studying the levels of development of dialogical speech in primary schoolchildren with intellectual disabilities (ID). In accordance with the purpose of the research, the following tasks were implemented: to carry out a theoretical analysis of the research problem; to develop criteria and indicators of the levels of dialogical speech development in younger schoolchildren with intellectual disabilities; to investigate the state and levels of development of dialogical speech in younger schoolchildren with intellectual disabilities in modern educational conditions. Materials and methods. To determine the levels of dialogical speech development, we have created a diagnostic program, criteria, and indicators for the development of dialogical speech in students with ID. Results. According to the results of the study, the high level of development of dialogical speech among primary schoolchildren with ID was not detected, 15.4 % of students showed sufficient level, 39.1 % - average level, 45.5 % had low level. Conclusion. Children with intellectual disabilities experience difficulties in independently formulating questions, choosing the necessary words in answers. In dialogue, younger schoolchildren with IP mostly use short, monotonous lines. Their answers are characterized by poor vocabulary, inaccurate use of words, morphological and syntactic agrammatism. This state of dialogical skills is due to the underdevelopment of coherent speech and basic mental operations such as analysis, synthesis, abstraction, generalization, comparison, systematization; inability to transfer acquired skills to a conversation situation, narrowing of verbal contacts, cognitive passivity. Their speech lacks emotion due to the inability of children with IP to use intonation.